2021
DOI: 10.1123/ijsnem.2020-0193
|View full text |Cite
|
Sign up to set email alerts
|

Higher Physical Activity Is Related to Lower Neck Adiposity in Young Men, but to Higher Neck Adiposity in Young Women: An Exploratory Study

Abstract: The role of lifestyle behaviors on neck adipose tissue (NAT), a fat depot that appears to be involved in the pathogenesis of different cardiometabolic diseases and in inflammatory status, is unknown. In this cross-sectional and exploratory study, the authors examined the relationship between sedentary time and physical activity (PA) with neck adiposity in young adults. A total of 134 subjects (69% women, 23 ± 2 years) were enrolled. The time spent in sedentary behavior and PA of different intensity were object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…20 Furthermore, increased NC in OSAS patients may be indicative of diminished aerobic capacity, reduced physical activity and fluid retention. 21,22 Prior research has established a connection between upper body subcutaneous fat (excluding abdominal fat) and aerobic capacity. 23 Hormonal fluctuations in OSAS patients, such as elevated cortisol levels, may contribute to fat accumulation in the neck and upper trunk, thereby influencing anthropometric indices.…”
Section: Osas and Neck Circumferencementioning
confidence: 99%
“…20 Furthermore, increased NC in OSAS patients may be indicative of diminished aerobic capacity, reduced physical activity and fluid retention. 21,22 Prior research has established a connection between upper body subcutaneous fat (excluding abdominal fat) and aerobic capacity. 23 Hormonal fluctuations in OSAS patients, such as elevated cortisol levels, may contribute to fat accumulation in the neck and upper trunk, thereby influencing anthropometric indices.…”
Section: Osas and Neck Circumferencementioning
confidence: 99%
“…12,[31][32][33][34][35] Although there are no studies that associate NC with gold standard indicators of total and central fat mass in pediatric population, two studies have shown the association of NC with bio-electrical impedance analysis technique in children and adolescents 16. In this context, Bammann et al investigated 78 preschool/school children aged 4-10 years, from four different European countries, and showed that NC is not the best predictor of fat mass (unadjusted R 2 =0.484) 36.…”
mentioning
confidence: 99%